La reparación integral derivada de la responsabilidad extracontractual del estado: la pertinencia de la vía administrativa o vía jurisdiccional - Arguello Escobar, Sebastian Fernando (2023)
ABSTRACT: The procedure of integral reparation, derived from the extra-contractual liability of the State, has two routes: 1. The administrative route and 2. The administrative judicial route. These two routes are established both in the Organic Administrative Code [COA] and in the General Organic Code of Proceedings [COGEP], under the protection of these legal bodies. Throughout the research, through the implementation of various methods, including inductive, legal-analytical, dogmatic, comparative-legal and comparative-legal, it has been possible to analyses the relevance of the administrative or contentious-administrative [jurisdictional] route in the integral reparation derived from the extra-contractual liability of the State. Within the framework of the research, the results obtained from the interviews, as a research tool applied to different specialists in the administrative and contentious-administrative fields, together with the respective analysis and discussion of the data, indicated that the contentious-administrative route is more relevant to ensure full reparation in cases of extra-contractual liability of the State.